E-Government: Efektivitas Layanan Aplikasi Pegadaian Syariah Digital Service (PSDS) pada Cabang Pegadaian Syariah Bogor Baru - Denia Maulani (Lembaga Pengembangan Manajemen dan Publikasi Imperium, 2020)
The development is currently growing very rapidly, this is evidenced by the progress in various fields, especially technology. However, not all technology provides convenience and a positive impact for its users if it is not handled properly. This study aims to determine the effectiveness of online services carried out by Pegadaian Syariah Bogor Baru Branch through the Mobile Pegadaian Syariah Digital Service (PSDS) application in increasing the number of customers. The method used is an approach to the theory of e-servqual and management functions. The method of data collection was carried out by making observations at the New Bogor Sharia pawnshop by conducting interviews and observations. The effectiveness of PSDS is reviewed through 7 dimensions, namely efficiency, reliability, compliance, privacy services, responsiveness, compensation, and contact.